Terdapat Hubungan Antara Jenis dan Frekuensi Olahraga dengan Tingkat Stres pada Mahasiswa Kedokteran di Bandung - Azmi Putri Azzahra; Lelly Yuniarti; Julia Hartati (UNISBA Press, 2023)
Abstract. Stress is one of the physiological reactions in an individual where various defense mechanisms occur to face situations that are considered threatening or increased demands. One of the ways to reduce stress levels is to exercise. Exercise will stimulate the production of beta-endorphin hormones which will have the effect of restoring mood and lowering cortisol levels. This research aims to analyze the relationship between the type and frequency of sports and the stress level of Faculty of Medicine students in Bandung. The research method used is descriptive comparative with cross-sectional. The subjects of this research are 135 students of the Faculty of Medicine in the City of Bandung, with simple random sampling. The type and frequency of sports were taken using the Godin Leisure-Time Exercise questionnaire, while the stress level was assessed using the Perceived Stress Scale. Data were analyzed with Fisher's Exact Test with a confidence level of 95% (α=0,05). The results of the research on the relationship between the type of sport and the level of stress obtained p=0.024 and the relationship between the frequency of sport and the level of stress obtained p=0.004. The conclusion of this research is that there is a relationship between the type and frequency of sports and the level of stress. Abstrak. Stres merupakan salah satu reaksi fisiologis pada suatu individu di mana terjadi mekanisme pertahanan yang beragam untuk menghadapi situasi yang dianggap mengancam atau tuntutan yang meningkat. Salah satu cara untuk menurunkan tingkat stres adalah berolahraga. Olahraga akan merangsang pengeluaran hormon beta-endorfin yang akan memberikan efek memulihkan suasana hati dan menurunkan kadar kortisol. Penelitian ini bertujuan untuk menganalisis hubungan jenis dan frekuensi olahraga dengan tingkat stres Mahasiswa Fakultas Kedokteran di Bandung. Metode penelitian yang digunakan adalah deskriptif comparative dengan cross-sectional. Subjek pada penelitian ini adalah Mahasiswa Fakultas Kedokteran di Kota Bandung berjumlah 135 orang, dengan pengambilan sampel secara simple random sampling. Jenis dan frekuensi olahraga diambil menggunakan kuisioner Godin Leisure-Time Exercise sedangkan tingkat stres dinilai menggunakan Perceived Stres Scale. Data dianalisis dengan uji Fisher’s Exact Test dengan tingkat kepercayaan 95% (α=0,05). Hasil penelitian hubungan jenis olahraga dengan tingkat stres didapatkan p=0.024 dan hubungan frekuensi olahraga dengan tingkat stres didapatkan p=0.004. Simpulan pada penelitian ini terdapat hubungan jenis dan frekuensi olahraga dengan tingkat stres.